Production and characterization of monoclonal antibodies to the protective antigen component of Bacillus anthracis toxin. - Little, S F (1988)
Thirty-six monoclonal antibodies to the protective antigen protein of Bacillus anthracis exotoxin have been characterized for affinity, antibody subtype, competitive binding to antigenic regions, and ability to neutralize lethal and edema toxin activities. At least 23 antigenic regions were detected on protective antigen by a blocking, enzyme-linked immunosorbent assay. Two clones, 3B6 and 14B7, competed for a single antigenic region and neutralized the activity of both the lethal toxin in vivo (Fisher 344 rat) and the edema toxin in vitro (CHO cells). These two antibodies blocked the binding of 125I-labeled protective antigen to FRL-103 cells. Our results support the proposal that binding of protective antigen to cell receptors is required for expression of toxicity.